PENGARUH LIKUIDITAS, SOLVABILITAS DAN PROFITABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN YANG TERDAFTAR DALAM INDEKS LQ 45 - Tiya, Tri Ade; Siahaan, Yansen; Jubi, Jubi; Manurung, Sepbeariska (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2018)
The purpose of this research is to describe liquidity,solvability, profitability and stock pricesand to know influence of liquidity, solvability and profitabilityto stock prices at the Companieslisted in LQ 45 Index.The research was using qualitative desriptive analysis and quantitative desriptive analysis. The data collection was using documentation. The analysis techniques used are multiple linear regression, correlation coeffient, coefficient of determination, hypothesis testing.The result of regression are liquidity, solvability and profitability have a negative effect on stock prices at the Companies listed in the LQ 45 Index.The results analysis of the correlation coefficient and determination coefficient is known that there is a medium relationship between liquidity, solvability and profitability of stock prices and stock prices are more influenced by other factors not examined in this research. The results of F testit is known that liquidity, solvability and profitability have a significant effect on stock prices at the Companies listed in the LQ 45 Index simultaneously. The results of the t test it is known that partially liquidity and solvability have a significant effect and profitability has no significant effect on stock prices at the Companies listed in the LQ 45 Index.The suggestion of this research is that the company should manage current assets optimally to increase revenue, control the use of debt, and distribute dividends to investors so that investors are interested in investing capital in the company.